Pelatihan Relaksasi Emosi melalui Teknik Square Breathing sebagai Upaya Meningkatkan Kestabilan Emosi pada Remaja - Eka Sufartianinsih Jafar; Novita Maulidya Jalal; Wilda Ansar; Irdianti Irdianti; Andi Nahliah Bungawali (Yayasan Literasi Sains Indonesia, 2026)
Adolescents are an age group that is prone to experiencing emotional instability due to academic pressure, social demands, interpersonal conflicts, and changes in psychological development. These conditions can have an impact on learning concentration, social relationships, and adolescent mental health, so simple strategies are needed to help regulate emotions. One technique that can be used is square breathing, which is a structured breathing exercise through the pattern of breathing, holding the breath, exhaling, and holding again in the same count. This community service activity aims to improve the understanding and regulation skills of adolescents through training in square breathing techniques. The implementation method uses a psychological education approach based on participatory training which was attended by 25 school-age adolescents. Activities include pre-tests, delivery of materials on mental health and emotional regulation, demonstration of square breathing techniques, hands-on practice, and post-tests. The results of the evaluation showed an increase in the average score of participants from 6 in the pre-test to 11 in the post-test or an increase of 83.33%. In addition, participants reported feeling more relaxed, calm, and focused after the exercise. The square breathing technique is considered effective as a simple strategy to help adolescents improve emotional regulation and reduce psychological tension.